2019
DOI: 10.1021/acs.est.9b00464
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Performance of Recyclable Amorphous MoS3 Supported on TiO2 for Capturing High Concentrations of Gaseous Elemental Mercury: Mechanism, Kinetics, and Application

Abstract: Hg0 capture by sorbents was a promising technology to control Hg0 emission from coal-fired power plants and smelters. However, the design of a high performance sorbent and the predicting of the extent of Hg0 adsorption were both extremely limited due to the lack of adsorption kinetics and structure–activity relationship. In this work, the adsorption kinetics of gaseous Hg0 onto MoS3/TiO2 was investigated and kinetic parameters were obtained by fitting breakthrough curves. According to the kinetic parameters, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 49 publications
5
130
0
Order By: Relevance
“…It has been reported that the initial pH value of the solution is an important factor which affects the photocatalytic performance. In general, the initial pH value affects the adsorption and dissociation behaviour of reactant molecules, the surface charge of the titanium dioxide, oxidation potential and other physico-chemical properties [37]. Besides, electrostatic attraction or repulsion between the catalysts and the reactant molecules results in an enhancement or suppression of the photocatalytic rate.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the initial pH value of the solution is an important factor which affects the photocatalytic performance. In general, the initial pH value affects the adsorption and dissociation behaviour of reactant molecules, the surface charge of the titanium dioxide, oxidation potential and other physico-chemical properties [37]. Besides, electrostatic attraction or repulsion between the catalysts and the reactant molecules results in an enhancement or suppression of the photocatalytic rate.…”
Section: Resultsmentioning
confidence: 99%
“…Four S 2p binding energies appeared on WS x /TiO 2 at 169.0, 164.3, 163.5, and 162.0 eV (Figure 3d) and were assigned to SO 4 2− , S 0 , S 2 2− , and S 2− , respectively. 18,33 Meanwhile, the Ti 2p binding energies at 462.4 and 456.1 eV corresponding to Ti−S cannot be observed in Figure S2a in the SI. 34 These suggest that S 2 2− and S 2− on WS x /TiO 2 were not bonded with Ti 4+ , and they were bonded to W 6+ .…”
Section: Industrial and Engineeringmentioning
confidence: 95%
“…The second type is a nonselective adsorption point, such as unsaturated coordination sites and lattice defects. 61 3.3.2. Intraparticle Diffusion Kinetic Model.…”
Section: Resultsmentioning
confidence: 99%
“…Because O* and Cl – have a massive affinity for Hg 0 .The selective adsorption points are multiplied by introducing HCl, NO, and SO 2 under O 2 /CO 2 combustion. The second type is a nonselective adsorption point, such as unsaturated coordination sites and lattice defects …”
Section: Resultsmentioning
confidence: 99%